2005
DOI: 10.1080/02713680590968529
|View full text |Cite
|
Sign up to set email alerts
|

Diode Laser Transscleral Cyclophotocoagulation for the Treatment of Refractory Glaucoma After Penetrating Keratoplasty

Abstract: Diode laser TSCPC appears to be a safe and effective procedure for the treatment of uncontrolled glaucoma secondary to penetrating keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
2
20
2
Order By: Relevance
“…The probability of graft survival was 79% at one year and 56% at five years [215]. Ocakoglu et al reported 97% of eyes with an IOP \22 mmHg at six months and 72% of eyes at twelve months with or without medications in patients undergoing CPC for refractory post-PKP glaucoma [216]. Another study reported IOPs of 6 to 21 mmHg were achieved in 79% of patients undergoing CPC for refractory post-PKP glaucoma with the need for re-treatment in 57% with a minimum of six months follow-up [217].…”
Section: Cyclodestructive Proceduresmentioning
confidence: 96%
“…The probability of graft survival was 79% at one year and 56% at five years [215]. Ocakoglu et al reported 97% of eyes with an IOP \22 mmHg at six months and 72% of eyes at twelve months with or without medications in patients undergoing CPC for refractory post-PKP glaucoma [216]. Another study reported IOPs of 6 to 21 mmHg were achieved in 79% of patients undergoing CPC for refractory post-PKP glaucoma with the need for re-treatment in 57% with a minimum of six months follow-up [217].…”
Section: Cyclodestructive Proceduresmentioning
confidence: 96%
“…[39][40][41][42][43][44] However, multiple treatments may be necessary and graft failure rates have been reported to be between 17 and 44%. [39][40][41][42][43][44] With 5-year follow-up, Beiran reported successful IOP reduction in patients with post-keratoplasty glaucoma using transscleral Nd:YAG laser in 63% of the patients. Fifty-six percent of these patients had clear grafts after 5 years.…”
Section: Cyclodestructive Proceduresmentioning
confidence: 99%
“…40 More recent studies on the use of diode laser to control post-keratoplasty glaucoma show a single treatment success rate of 72% after 12 months with no cases of graft failure or phthisis bulbi. 43 In a small series, Ayyala reported no differences between trabeculectomy with mitomycin C, cyclophotocoagulation, and glaucoma shunt procedures to control glaucoma after keratoplasty. 39 …”
Section: Cyclodestructive Proceduresmentioning
confidence: 99%
“…Because it is a destructive procedure, trans-scleral cyclophotocoagulation has traditionally been used to permanently reduce high intraocular pressures in non-seeing eyes with poor prognosis or to relieve refractory glaucoma when other more conservative measures have failed. Serious side effects can occur with traditional TS-CPC like hypotony, vision loss, iritis, and rarely sympathetic ophthalmia and pthisis bulbi [2].…”
Section: Introductionmentioning
confidence: 99%